Hubungan Intensitas Bermain Game Online Slot dengan Prokrastinasi Akademik pada Remaja di Kota Padang Panjang - Vanesya Sabilla HR; Zulian Fikry (Departement of Mathematics Education, 2023)
The purpose of this study to determine the relationship between intensity of playing online slot games and academic procrastination among adolescents in the city of Padang Panjang. This research is a quantitative correlational research with sample selection using incidental sampling technique. The number of samples in this study were 125 subjects. This study uses a modified Internet Gaming Disorder scale and an academic procrastination scale. Data analysis techniques in this study used product moment correlation with the help of SPSS version 16.0 for Windows. Based on the results of this study obtained a correlation coefficient value of 0,475 and p value = 0,000 (p < 0,05), so Ha accepted. This means that, there is a significant positive relationship between the intensity of playing online slot games and academic procrastination in adolescents in the city of Padang Panjang.